Algorithm for optimal urethral coverage in hypospadias and fistula repair: a systematic review - Fahmy, Omar; Khairul-Asri, Mohd Ghani; Schwentner, Christian; Schubert, Tina; Stenzl, Arnulf; Zahran, Mohamed Hassan; Gakis, Georgios (Elsevier BV, 2016)
Context: Although urethral covering during hypospadias repair minimizes the incidence of fistula, wide variation in results among surgeons has been reported.